Penerapan Model POE Berbantuan Media Realia untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Safitri, Islamiati; Sulistri, Emi; Prihatiningtyas , Nindy Citroresmi (Scholarly Journal of Elementary School, 2024)
This study aims to: 1) to determine the increase in students' creative thinking skills after applying the realia media-assisted POE model to style material; 2) to find out the implementation of the POE learning model assisted by realia media on style material. The research used is quantitative research with the design of One Group Pre Test Post Test. The population in this study were fourth grade students at SDN 09 Semelagi. The research sample was taken by purposive sampling. The analysis of the test for creative thinking ability in the first formulation uses the normalized N-gain equation and for the second formulation uses the calculation of the percentage of model implementation. The results showed that: 1) from the results of the calculation of the average N-gain students' creative thinking ability of 0.6 which is in the medium category, meaning that the realia media-assisted POE learning model can improve students' creative thinking abilities after the application of the media-assisted POE learning model realia on the material style; 2) the average implementation calculation is 88% with very good criteria, meaning that the POE learning model assisted by realia media is implemented very well in style material in class IV SDN 09 Semelagi.